Implementation of GIS Application for Water Company Needs - Mickrenska‑Cherneva, Christina; Mladenov, Radoslav (Geomatics and Environmental Engineering, 2020)
The process of designing and implementing industrial models (or GIS) for underground utility infrastructure (UUI) includes a number of activities related to the analysis of source data to identify objects, pre‑processing the initial data, creating spatial database and development of relevant graphic (maps) and text (registers) products. Nowadays, every organization needs to be flexible and able to respond in a timely and adequate manner to the changes that occur in a complex and dynamic external environment. This is the reason why the paper proposes an approach for the design and development of a geoinformation system (GIS), through the capabilities of modern software for a part of the water supply and sewerage network for the needs of Water Supply and Sewerage Berkovitsa LTD. The purpose of the paper and GIS for maintaining data on UUI is to provide access to digital data for underground utility infrastructure and their characteristics, as well as to assist in the easy creation of references to underground utility infrastructure data in digital and graphic form.